Endovascular therapy for distal hilar renal artery aneurysm: a case report and literature review. Issue 1 (January 2022) - Ye, Pin; Wu, Hongxiao; Chen, Yunfei; Li, Yiqing; Cai, Chuanqi; Lv, Ping
Renal artery aneurysm (RAA), a type of visceral aneurysm with atypical symptoms, is difficult to detect and is usually discovered incidentally by imaging examination. Hilar RAA (HRAA) represents a relatively rare subgroup of RAA that is located in the distal part of the renal artery, close to the renal parenchyma. We reported a 55-year-old woman with an HRAA measuring 19 mm × 20 mm × 20 mm. She underwent endovascular therapy with bare-metal stent implantation with nested coil embolization. She was discharged without complications. The uniqueness of this case is the aneurysm location, which was at the distal right renal artery, making it difficult to preserve the blood supply to the right kidney. The novelty of the minimally invasive technique was that this endovascular treatment not only eliminated the aneurysm, but also preserved the blood supply to the ipsilateral kidney. Endovascular therapy is effective in the management of HRAA.